If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2x+7=3
We move all terms to the left:
x+2x+7-(3)=0
We add all the numbers together, and all the variables
3x+4=0
We move all terms containing x to the left, all other terms to the right
3x=-4
x=-4/3
x=-1+1/3
| 22=5b-13 | | 169+8=2(8p+4) | | -2w+34=2(w-3) | | 0.96y-0.78=0.21y+0.46 | | 11+6k=36 | | Z=-4a-2 | | -34=b^-6 | | 2x-4=3x=19 | | 2,970=45(p+15) | | 413+x-6241=2000 | | 8x-2x-4+5=108 | | 52x+128=24 | | -2(v+6)=-7v+28 | | 5/6x=-7/8 | | 13=4(5x+1)+11x | | 7(2x–5)=28 | | 9x-7x-5-3=-7x-4x+5 | | 1/6m+5/6m-5/6(m+1)=1/6(5m+1) | | 6(b-5)+b2=82 | | 1/2x-10=27 | | 9x2−1=0 | | 2x-4=3x-25 | | 24=-8u+6(u+6) | | 1,128=6(x+19) | | -13=4(5x+-1-11x | | m/6=34 | | -5-12=2y+30 | | 10(w-8)=-160 | | A(p)=p2+9p+20 | | 0=(x^2)-2x-8 | | 6d=9=39 | | 12-8g=-92 |